Primary Percutaneous Coronary Intervention in Patients With Type 2 Diabetes With Late/Very Late Stent Thrombosis and de novo Lesions: A Single-Center Observational Cohort Study of Clinical Outcomes and Influencing Factors - Zhao, Xiaoxiao; Lan, Jun; Yu, Xiaoping; Zhou, Jinying; Tan, Yu; Sheng, Zhaoxue; Li, Jiannan; Wang, Ying; Chen, Runzhen; Liu, Chen; Zhou, Peng; Chen, Yi; et al. (Frontiers in Cardiovascular Medicine, 2021)
Abstract BACKGROUND: This study aimed to compare differences in the risk factors and clinical outcomes of type 2 diabetes mellitus (DM) and non-DM patients with de novo lesions (DNL) and definited late or very late stent thrombosis (LST/VLST). METHODS: A total of 4151 patients with acute coronary syndrome were screened angiographically to determine DNL and LST/VLST. A total of 3941 patients were included in the analysis and divided into DM (n=1286) or non-DM (n=2665) group at admission. The primary endpoint was a composite of major adverse cardiovascular events (MACEs), defined as death, myocardial infarction, revascularization, and ischemic stroke within a 1-year follow-up period. RESULTS: In the group with total white blood cell count >10 10^9/L (p=0.004), neutral granular cell count >7 10^9/L (p=0.030), neutrophil-lymphocyte ratio >1.5 (p=0.041), DNL outperformed LST/VLST lesions in terms of revascularization at a median follow-up of 698 days. Among patients with DNL, the incidences of MACEs (log-rank p=0.0002), all-cause death (log-rank p=0.00032), cardiac-related death (log-rank p=0.021), and revascularization (log-rank p=0.029) were significantly lower in the non-DM group than in the DM group. However, no difference was observed in the event rates of endpoints among patients with LST/VLST between the non-DM and DM groups. CONCLUSION: This study found that DM patients have a higher incidence of composite clinical outcomes than non-DM patients among patients with DNL. Compared with patients with DNL, patients with LST/VLST lesions had more incidence of revascularization by long-term follow up.